New perspectives and evaluation of training for Event Management - Kovac, Tanja (Technium Social Sciences Journal, 2020)
The purpose of this research was to identify opportunities for Event Managers to gain certification and recognition for their knowledge, skills and competences. The results of the research can represent a base for developing a National Qualifications Standard of Event Management, and a reference to develop the European Qualification Framework (INVENT 2017-1-UK01-KA202, 2018). The aim of this research was to determine an effective view of Event Management and the Event Manager’s career path for future reference. The survey showed some gaps in formal and informal educational programs of Event Management in Slovenia, and some suggestions to improve the quality of that field and how to train the teachers who train Event Managers follow. To evaluate the hypothesis, a model for assessing education programs of event management has been developed, using the computer program Dexi. This instrument serves to verify the presence or absence of skills from the National Qualification Standard. The system allows you to check if the quality of the education program is appropriate, and what needs to be done to improve the quality.